Nell's mom: 30 mL for 2 ounces = 15 mL for 1 ounce
Nell's dad: 65 mL for 5 ounces = 13 mL for 1 ounce
15 > 13
Therefore, Nell's mom's chocolate milk is more chocolately.
........Option C ) n × 2 = t
Answers: height, "h", of a triangle: <span> h = 2A / (b₁ + b₂) .
___________________________________________________ </span>
Explanation:
__________________________________________________
The area of a triangle, "A", is equal to (1/2) * (b₁ + b₂) * h ;
or: A = (1/2) * (b₁ + b₂) * h
or: write as: A = [(b₁ + b₂) * h] / 2 ;
___________________________________________
in which: A = area of the triangle;
b₁ = length of one of the bases
of the triangle ("base 1");
b₂ = length of the other base
of the triangle ("base 2");
h = height of the triangle;
____________________________________________________
To find the height of the triangle, we rearrange the formula to solve for "h" (height); assuming that all the units are the same (e.g. feet, centimeters); if no "units" are given, then the assumption is that the units are all the same.
We can use the term "units" if desired, in such cases; in which the area, "A" is measured in "square units"; or "units²",
_________________________________
So, given our formula for the "Area, "A"; of a triangle:
_________________________________________________
A = [(b₁ + b₂) * h] / 2 ; we solve for "h" in terms of the other values; by isolating "h" (height) on one side of the equation.
If we knew the other values; we plug in the those other values.
______________________________________________
Given: A = [(b₁ + b₂) * h] / 2 ;
Multiply EACH side of the equation by "2" ;
_________________________________________
2*A = { [(b₁ + b₂) * h] / 2 } * 2 ;
_________________________________________
to get:
_________________________________________
2A = (b₁ + b₂) * h ;
_____________________________________________________
Now, divide EACH side of the equation by: "(b₁ + b₂)" ; to isolate "h"
on one side of the equation; and solve for "h" (height) in terms of the other values;
_____________________________________
2A / (b₁ + b₂) = [ (b₁ + b₂) * h ] / (b₁ + b₂);
______________________________________
to get:
_______________________________________________
2A / (b₁ + b₂) = h ; ↔<span> h = 2A / (b₁ + b₂) .
__________________________________________________</span>
Answer:
9lb chocolate candies
6lb sugar candies
Step-by-step explanation:
Yes, I also happen to go to RSM. (6b)
Equation: 7x+2(15-x)=5*15
Solve:
7x+(2)(15)+(2)(−x)=(5)(15)
7x+30+(−2x)=75
(7x+(−2x))+(30)=75
5x+30=75
5x=45
x=9lb chocolate candies
Now, calculate the sugar candies.
15-9=6lb sugar candies
No because 5^2 +10^2 is not equavalent to 13^2
by using the pythagoras' theorem